Anticodon loop size and sequence requirements for recognition of formylmethionine tRNA by methionyl-tRNA synthetase. - Schulman, L H (1983)
Previous work from our laboratory identified several specific sites in Escherichia coli tRNAfMet that are essential for recognition of this tRNA by E. coli methionyl-tRNA synthetase (EC 6.1.1.10). Particularly strong evidence indicated a role for the nucleotide base at the wobble position of the anticodon in the discrimination process. To further investigate the structural requirements for recognition in this region, we have synthesized a series of tRNAfMet derivatives containing single base changes in each position of the anticodon. In addition, derivatives containing permuted sequences and larger and smaller anticodon loops have been prepared. The variant tRNAs have been enzymatically synthesized in vitro. The procedure involves excision of the normal anticodon, CAU, by limited digestion of intact tRNAfMet with pancreatic RNase. This step also removes two nucleotides from the 3' CpCpA end. T4 RNA ligase is used to join oligonucleotides of defined length and sequence to the 5' half-molecule and subsequently to link the 3' and modified 5' fragment to regenerate the anticodon loop. The final step of the synthesis involves repair of the 3' terminus with tRNA nucleotidyltransferase. The synthetic derivative containing the anticodon CAU is aminoacylated with the same kinetics as intact tRNAfMet. Base substitutions in the wobble position reduce aminoacylation rates by at least five orders of magnitude. The rates of aminoacylation of derivatives having base substitutions in the other two positions of the anticodon are 1/55 to 1/18,500 times normal. Nucleotides that have specific functional groups in common with the normal anticodon bases are better tolerated at each of these positions than those that do not. A tRNAfMet variant having a six-membered loop containing only the CA sequence of the anticodon is aminoacylated still more slowly, and a derivative containing a five-membered loop is not measurably active. The normal loop size can be increased by one nucleotide with a relatively small effect on the rate of aminoacylation, indicating that the spatial arrangement of the nucleotides is less critical than their chemical nature. We conclude from these data that recognition of tRNAfMet requires highly specific interactions of methionyl-tRNA synthetase with functional groups on the nucleotide bases of the anticodon sequence.